Perbandingan pemberian minyak kuning telur ayam dan bioplacenton terhadap gambaran histologi kulit - Ratna Widyawati; Rondius Solfaine; Dian Ayu Kartika Sari; Yoko Shagita (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
This study was conducted to determine the comparison of re-epithelialization, granulation and the number of inflammatory cells infiltration between topical application of chicken yolk oil and bioplacenton on white rat (Rattus norvegicus) skin that has induced with second degree burn wound. This research was a laboratory experimental study using 18 male white rats divided into control positive (K+) group, bioplacenton (P1) and chicken yolk oil (P2). Observation of the re-epithelialization, granulation and inflammatory cells infiltration were carried out 14 days after the rat were induced with second degree burn wound. The necropcy was performed on the 14th day and then the skin organs were treated with HE staining and observed under a microscope. Data analysis was performed using Kruskal-Wallis followed by Mann Whitney. The results of the analysis showed that K + had significantly different results (P <0.05) compared to P1 and P2 in the scores of re-epithelialization, granulation and the number of inflammatory cell infiltrations. P1 and P2 were not significantly different (P> 0.05). In this study, it can be concluded that chicken egg yolk has a comparable effect with bioplacenton toward the score of re-epithelialization, granulation and the number of inflammatory cell infiltration.